Adsorption of HDTMA-Br surfactant with concentration variation by rice husk-based activated carbon produced by variation of carbonization temperature - Galih N. R. Pargiman; Arnelli Arnelli; Yayuk Astuti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Research has been conducted on the adsorption of HDTMA-Br surfactant by rice husk-activated carbon with variation of carbonization temperature and concentration of HDTMA-Br. This study aims to produce surfactant modified activated carbon (SMAC), therefore it is necessary to determine the influence of carbonization temperature to the adsorption capability of activated carbon on HDTMA-Br surfactant by identifying the amount of HDTMA-Br surfactant absorbed, to characterize the characters of carbon, activated carbon and activated carbon adsorbing surfactant using FTIR and SAA. Carbonization was carried out by pyrolysis with temperature variations of 300, 350 and 400°C. The carbon produced was activated using 60% H3PO4 for 1 hour. After that, the activated carbon was applied to adsorb HDTMA-Br surfactant by varying the concentration that were 300, 1100, 1900, 2700, 3500 and 4300 ppm. The results showed that HDTMA-Br adsorbed tended to increase by increasing the concentration of surfactant. In addition, the best carbonization temperature showing high adsorption capability of activated carbon was at 300°C. FTIR spectra of activated carbon showed the presence of P = O peak; at the SMAC sampel there was peak of N-(CH3)3 with different intensities in three samples. Moreover, SAA analysis showed that the surface area of activated carbon increased compared to carbon and slightly decreased after the activated carbon absorbed HDTMA-Br.